Optimization of Cross-linking Modification on Canna Starch with Sodium Acetate Using Response Surface Methodology - Iffah Muflihati; Nur Khikmah (BRIN, 2022)
Canna starch is obtained from the extraction of canna tubers. However, the unstable native of canna starch during processing makes its use limited. Crosslinking starch can make starch resistant to shear stress acid resistance and prevent viscosity decrease due to the rupture of starch granules during heating. The purpose of this study was to obtain the optimum conditions of concentration and duration of mixing sodium acetate for cross-linking modification of canna starch with viscosity as the primary response. This study used a factor of sodium acetate concentration and mixing time. The modification of canna starch by cross-linking affects the viscosity. Cross-linking in starch can strengthen the starch granules so that the starch granules are not easily gelatinized. The optimum viscosity condition was obtained from a sodium acetate concentration of 16.21% with a mixing time of 20.71 minutes to get the optimum viscosity of 43.7 cP. The high degree of substitution of sodium acetate in cross-linking modification affects the integrity of starch granules, where starch granules can affect the physicochemical characteristics of starch. The higher the DS value, the lower the amylose content and the solubility. However, increasing the degree of substitution can also increase the viscosity, swelling power, syneresis, and pH of the cross-linked modified starch. Keyword: Canna starch, cross-linking, optimization, sodium acetate.